Systems estimation of a structural model of distribution and demand in the US economy - Robert A. Blecker; Michael Cauvel; Yun Kim (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2020)
Empirical studies of income distribution and aggregate demand using a structural modeling approach typically find that demand is wage-led in most large, advanced economies. These studies have been criticized for estimating the individual equations for consumption, investment, and net exports separately, treating total output and the wage share as exogenous, which could lead to simultaneity bias. This paper corrects for such possible bias as well as common shocks to the equations by using systems GMM estimation applied to annual US data for 1963-2016. This paper is also the first to provide separate estimates of nonresidential and residential investment functions and to distinguish the effects of shocks to different underlying determinants of the wage share (unit labor costs and firms' monopoly power). Surprisingly, the GMM estimates imply that private-sector aggregate demand is more, rather than less, wage-led (or in some cases, less profit-led) compared with OLS estimates of identically specified models.
Keywords: E12; E25; N12; O51; C36; 330; income distribution; wage-led demand; profit-led demand; US economy; systems estimation